Numerical Modeling Of Freezing Water Droplets - Magalhães, Leandro (2022)
This work enhances the understanding of droplet dynamics under cryogenics conditions through an in-house developed analytical tool used to predict the supercooling of water droplets. The physical process is based on a full-scale four-stage supercooling process in which the recalescence stage is assumed instantaneous and the crystallization kinematics of the droplet neglected. The transition temperature of each stage is obtained, resorting to a theoretical balance for the droplets internal energy against the heat loss to the environment. In this way, the representation for the droplets temperature curves alongside the time. The droplets are considered spherical, and the internal motion is so vigorous that complete mixing occurs. The droplets convective effects are accounted for using the Ranz-Marshall classical formulation.